Chemical Composition and Sensory Evaluation of Products Made From Oats (Avena Sativa) and Unripe-Plantain (Musa Paradisiaca) - Nkechi G. Onyeke; Nkechi G. Onodugo; Scholastica N. Eze; Linda O. Okoye (International Journal of Home Economics, Hospitality and Allied Research)
The study accessed the chemical composition and sensory evaluation of products made from oat (Avena sativa) and unripe plantain (Musa paradisiaca). This research aimed to determine the chemical composition of food products made from unripe plantain and oat composite flours and evaluated the acceptability of such foods through sensory evaluation for the benefits of diabetics and obese persons. Proximate, minerals, and phytochemicals analysis were conducted to ascertain the concentration of essential nutrients composition, Unripe plantain and oats flours were mixed at 50:50, 70:30, and 80:20 in ratios of plantain and oats respectively to formulate the composite flours, and analysed to determine the most preferable and recommend ratio based on chemical composition and sensory properties. Composite flour mixes with 50:50 in ratio proved to be the most preferable in sensory evaluation, general acceptability, minerals composition, and the proximate; it is then recommended for the target population. Unripe plantain and oats composite flours when adopted as part of food varieties or food ingredients for diabetics and obese persons can be used to make foods whether as deserts or main meal components of their diets in form of puddings, dumplings, and swallows.